Growth regulation and off-season flowering through night breaks in Chrysanthemum morifolium Ramat cv. Anmol - Thakur, Tanya; Grewal, HS (Bangladesh Journal of Botany, 2019)
The photoperiodic night interruption to schedule efficient flowering time in Chrysanthemum morifolium Ramat cv. Anmol according to demand of its flowers in the market was monitored. The influence of six night interruption treatments i.e. control, <5 second flash, 30, 60, 90 and 120 min were studied on the morphological development of Chrysanthemum morifolium Ramat cv. Anmol. The results revealed that the plant height, number of branches, leaves and root suckers per plant were positively affected with increased duration of night interruption. The flowering time was significantly delayed from mid December to end of February (two months) and number of flowers per plant increased as the duration of night interruption was increased from control to 120 min. Therefore, the night interruption durations studies were helpful to schedule the sustainable flowering time in Chrysanthemum cultivar Anmol by around two months with better plant growth.